Menstrual Personal Hygiene Behavior Among Adolescents with Physical and Intellectual Disabilities - Elfiyani, Nur Khotimah; Kusumayati, Agustin; Wuryaningsih, Caroline Endah; Siregar, Kemal Nazaruddin (UI Scholars Hub, 2024)
Reproductive health for adolescents with disabilities is often disregarded, and education on personal hygiene is insufficient because some people perceive menstruation as a sensitive topic and have a false belief that adolescents with disabilities have no sexual desire. This study aimed to determine the overview of personal hygiene behavior among adolescents with physical and intellectual disabilities when facing menstruation. The method used was qualitative, with case studies, in-depth interviews, and observations for data collection. The informants comprised four adolescents aged 19-21 years, two mothers, and two therapists for special needs children. This study was conducted at two growth and development clinics in South Jakarta, Indonesia, from July to September 2021. This study found a lack of apprehension about menstrual personal hygiene among mothers and adolescents with disabilities, a lack of understanding about menstrual personal hygiene in general among adolescents with disabilities, and inappropriate menstrual personal hygiene behavior among adolescents with disabilities. To conclude, this study underlines the importance of improving the ability of adolescents with disabilities in terms of menstrual hygiene behavior.